2018
DOI: 10.1177/0269215518784338
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of highly challenging balance training in Parkinson’s disease—a randomized controlled trial

Abstract: These results suggest that training effects diminish within 6 months after balance training, implying that the program may need to be repeated regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 31 publications
3
76
0
4
Order By: Relevance
“…on the PDQ-39. A 6-week intervention period may be too brief to observe noticeable changes in clinical or perceived measures (8,18,(45)(46)(47)(48)(49). In addition, as the ABC-C intervention was carried out as group exercise, including participants with different disease severity and cognitive abilities in the same group, the program may have been less challenging for people with milder disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…on the PDQ-39. A 6-week intervention period may be too brief to observe noticeable changes in clinical or perceived measures (8,18,(45)(46)(47)(48)(49). In addition, as the ABC-C intervention was carried out as group exercise, including participants with different disease severity and cognitive abilities in the same group, the program may have been less challenging for people with milder disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…All patients included in the RCTs were on a stable medication regimen. [18][19][20][21][22][23][24][25][26][27][28] With the exception of one study, all other studies involved assessments at the 'on' status of medications. 29 As shown in Table 1, the interventions in the experimental group involved two different types of tasks, whereas the control group either performed one type of approach or maintained regular activities.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…In addition to one study that applied the Balance Evaluation Systems Test to assess balance, 25,37 there were three studies that used the Mini-Balance Evaluation Systems Test. 24,26,29 Therefore, these studies were included in our meta-analysis. Results from the randomeffects model indicated that dual-task training had a significant improvement on balance function compared with that of the control groups (SMD, −0.44; 95% CI, −0.84 to −0.05; P = 0.03; I 2 , 56%; Figure 3), indicating large heterogeneity in terms of this parameter.…”
Section: Outcome Measures and Main Findings Of Included Studiesmentioning
confidence: 99%
“…Because these axial symptoms only improve partially with dopaminergic medication [2,[5][6][7][8], non-pharmacological interventions such as physiotherapy are important to manage these problems [9][10][11][12]. There is growing evidence that physiotherapy interventions improve gait [13][14][15][16][17][18][19] and balance performance in PD [20][21][22][23][24][25][26][27][28]. Physiotherapy typically involves functional gait and balance exercises [9,10,24] that translate directly to daily life activities [29][30][31].…”
Section: Introductionmentioning
confidence: 99%